Geometrical reconstruction of fluorescence events observed by the LHAASO experiment *Supported by National Natural Science Foundation of China (11903005, 11563004, 11475190). (April 2021) - Aharonian, F.; An, Q.; Axikegu,; Bai, L. X.; Bai, Y. X.; Bao, Y. W.; Bastieri, D.; Bi, X. J.; Bi, Y. J.; Cai, H.; Cai, J. T.; Cao, Z.; et al.
Abstract: The LHAASO-WFCTA experiment, which aims to observe cosmic rays in the sub-EeV range using the fluorescence technique, uses a new generation of high-performance telescopes. To ensure that the experiment has excellent detection capability associated with the measurement of the energy spectrum, the primary composition of cosmic rays, and so on, an accurate geometrical reconstruction of air-shower events is fundamental. This paper describes the development and testing of geometrical reconstruction for stereo viewed events using the WFCTA (Wide Field of view Cherenkov/Fluorescence Telescope Array) detectors. Two approaches, which take full advantage of the WFCTA detectors, are investigated. One is the stereo-angular method, which uses the pointing of triggered SiPMs in the shower trajectory, and the other is the stereo-timing method, which uses the triggering time of the fired SiPMs. The results show that both methods have good geometrical resolution; the resolution of the stereo-timing method is slightly better than the stereo-angular method because the resolution of the latter is slightly limited by the shower track length.